THE INVENTORY AND HIERARCHY OF GEOMORPHOSITES IN THE VLĂDEASA MASSIF - GABRIELA COCEAN (Revue Roumaine de Géographie)
At first glance, the Vlădeasa Massif does not stand out in the Apuseni Mountains in terms of the number of geomorphosites it contains, nor in terms of their diversity. But, if one carefully analyzes the landforms in this area, one would find a surprisingnumber of landmarks that could be classified as geomorphosites. Karstic landforms are the most numerous among these, surprisingly one may add, for a massif that is mainly build up by volcanic rocks and crystalline schists. The karst geomorphosites are all situated in the limestone area of the massif, the Stanciului Valley. After a diagnosis performed on these potential geomorphosites, using the method already successfully applied for the Trascău Mountains, the list of geomorphosites in the Vlădeasa Massif, containing 20 such sites was generated. Most of them are endokarstic forms: caves, potholes and swallets, but there are also peaks, one waterfall and some valley sectors. Among these, the top three sites could occupy leading positions in a hierarchy of geomorphosites in the Apuseni Mountains due to their unique features, and high values: VârfuraşuCave, Răchiţele Waterfall and Pietrele Albe klippes